2017
DOI: 10.1063/1.4974946
|View full text |Cite
|
Sign up to set email alerts
|

Temperature effect on lattice and electronic structures of WTe2 from first-principles study

Abstract: Tungsten ditelluride (WTe2) exhibits extremely large and unsaturated magnetoresistance (MR). Due to the large spatially extensions of Te-5p and W-5d orbitals, the electronic properties of WTe2 are sensitive to the lattice structures, which can probably affect the strongly temperature dependent MR found in experiment.Based on first-principle calculations, we investigate the temperature effect on the lattice and electronic structures of WTe2. Our numerical results show that the thermal expansion coefficients of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Technically however, it is highly unlikely that WTe 2 shows a temperature dependent band structure as it neither shows structural nor electronic phase transition down to the lowest possible temperature from the room temperature [1,32]. In agreement with this view, a recent band structure study using firstprinciple calculations with the inclusions of temperature effect suggests for no dramatic changes in the band structure of WTe 2 below 300 K [33]. Hence, it is interesting to study the band structure of WTe 2 as a function of temperature to reveal the discrepancies between the experiment and the theory and to further understand the origin of XMR.…”
Section: A Introductionmentioning
confidence: 90%
“…Technically however, it is highly unlikely that WTe 2 shows a temperature dependent band structure as it neither shows structural nor electronic phase transition down to the lowest possible temperature from the room temperature [1,32]. In agreement with this view, a recent band structure study using firstprinciple calculations with the inclusions of temperature effect suggests for no dramatic changes in the band structure of WTe 2 below 300 K [33]. Hence, it is interesting to study the band structure of WTe 2 as a function of temperature to reveal the discrepancies between the experiment and the theory and to further understand the origin of XMR.…”
Section: A Introductionmentioning
confidence: 90%
“…Another important feature of the MR in WTe 2 can be manifested by its strong dependence on temperature. This behavior has been proposed to arise from the temperature-dependent electronic band structure of WTe 2 . ,, However, recent works , have shown that the temperature has a negligible effect on the band structure of WTe 2 . The achieved charge compensation in our samples also allows us to explicitly study the effect of temperature on the MR and carrier dynamics.…”
mentioning
confidence: 99%
“…Besides the unique electronic structure and large lattice expansion, other effects such as charge localization or delocalization and similar temperature effects in degenerate semiconductor as proposed to explain the temperature‐induced Lifshitz transition in (Zr, Hf)Te 5 cannot be fully excluded from the mechanism of temperature‐induced Lifshitz transition in T d ‐WTe 2 . We note that a recent DFT calculation fails in reproducing the observed band evolution, possibly because it used a much smaller volume expansion coefficient obtained from calculation (about 1.7 × 10 −5 /K compared with 7.2 × 10 −5 /K from our experiment).…”
mentioning
confidence: 82%